2013
DOI: 10.1103/physreva.87.032716
|View full text |Cite
|
Sign up to set email alerts
|

Doubly differential distribution of electron emission in ionization of uracil in collisions with 3.5-MeV/u bare C ions

Abstract: We report the energy and angular distribution of the electron emission from an RNA base molecule uracil in collisions with 3.5-MeV/u bare C ions. The absolute double differential cross sections (DDCS) are measured for emission energy between a few to 600 eV. The angular distributions are compared to those obtained for the O2 molecule in the same experiment. The single differential cross sections (SDCS) are also deduced. The energy and angular distributions of the DDCS and SDCS are compared with the state-of-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 52 publications
(88 reference statements)
2
45
1
Order By: Relevance
“…[40] for details). The same spectrometer has been widely used to investigate several features of Coulomb ionization in ion-atom or ion-molecule collisions using He, Ne, H 2 , or other heavier atoms and large biomolecules [1,38,[40][41][42]. However, in order to compare the shape of the two spectra arising from Ne and C 60 , the Ne data was normalized to that for C 60 at a given energy since the gas density, path length, and solid angles were different for the two cases.…”
Section: Experimental Details and Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…[40] for details). The same spectrometer has been widely used to investigate several features of Coulomb ionization in ion-atom or ion-molecule collisions using He, Ne, H 2 , or other heavier atoms and large biomolecules [1,38,[40][41][42]. However, in order to compare the shape of the two spectra arising from Ne and C 60 , the Ne data was normalized to that for C 60 at a given energy since the gas density, path length, and solid angles were different for the two cases.…”
Section: Experimental Details and Measurementmentioning
confidence: 99%
“…The interest in these systems arises since one needs to understand the influence of the many-body nature on ionization and charge-transfer processes. In a recent study, it was shown that uracil, which is a ring-shaped organic molecule, has a dramatically large cross section for electron emission, particularly at forward angles, and this behavior cannot be explained in the realm of conventional ion-atom collision models [1]. Similarly, the collective excitation in polycyclic aromatic hydrocarbon (PAH) molecules [2], found in the interstellar medium, also influences their interaction with charged particles and photons.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies attention has turned to more complex systems, for instance collisions with large biomolecules [16,[20][21][22]. The experiments cover a wide energy range from a few keV up to ca.…”
Section: Introductionmentioning
confidence: 99%
“…100 MeV. Ionization by bare ions was investigated in detail by Tribedi and co-workers for a wide range of targets with emphasis on the two-center (TCE) and interference effects [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation